Detection of Prostate Cancer and Benign Prostatic Hyperplasia Using Prostate-Specific Antigen Testing: A Review of Clinical Research Studies - Islam, Md Azizul; Haque, Md Jawadul; Hossain, Mokther; Islam, S M Shahinul (Journal of Bio-Science, 2024)
The most often diagnosed diseases in males, prostate cancer (Ca-P) is now the third most common malignancy to cause mortality in different countries of the world. Data showed that serum PSA and prostate volume were demonstrated a substantial log-linear association with age. Numerous studies have demonstrated that the level of fPSA and the ratio of fPSA/total PSA can distinguish between benign and malignant prostatic diseases, with much lower levels in patients with prostate cancer. In a group of 681 LUTS patients, researcher assessed total PSA, fPSA, and prostate volume. The prostate volume significantly correlated with both total serum PSA and free PSA, with r = 0.51 (p<0.001) and r = 0.61 (p<0.001), respectively. In the range of 10% to 20% of the observed prostate volume, fPSA produced 67% of the anticipated values and 91.2% of the actual results. For intervals of between 10% and 20%, total serum PSA was predicted to increase at rates of 63.0% and 90.9%, respectively. It is known that early-stage prostate cancer tumours release PSA, which can be used as a biomarker to track treatment response and disease progression and to help doctors make treatment decisions. Data shows before surgery, PSA levels can be used to forecast how radical prostatectomy would turn out. Preoperative PSA levels were substantially correlated with advanced, high-grade illness and biochemical markers. The usefulness of PSA as a prognostic indicator declines with prostate cancer progression. As the disease progresses, prostate cancer tumours become significantly more heterogeneous, both between patients and, crucially, within the same patient. This causes variation in tumour PSA expression, which may cause false positive or false negative PSA test findings. In symptomatic patients, PSA has a high sensitivity and a low specificity for the detection of prostate cancer. There is an urgent need for research into the usefulness of PSA for the detection of clinically relevant prostate cancer in primary care. J. Bio-Sci. 31(2): 56-66, 2023